L'erotisme a les Cartes a les Senyores dels Àngels i de Jerusalem, de Francesc Fontanella. - SOGUES, MARC (Scripta, 2014)
This article focuses on the study of the treatment of eroticism in some of the poetic compositions from Francesc Fontanella (1622-1682/3). The paper studies fiften literary epistles whisch Fontanella dedicated to the nuns of the convent of Els Àngels and Jerusalem of Barcelona during the 1640s. It is divided into two parts; to first, the compositions under study are identified and presented briefly, and some issues related to the transmission of these textes are clarified. The second part discusses in detail all erotic references present in text. This analysis, on one hand, allows to present an interpretation of the meaning of the whole story contained in the letters. Moreover, it allows to present a characterization of the erotic vision of Fontanella. This is done by comparing this vision with the usual one at the time of baroque, as well as by analyzing the rhetorical strategies and the representation strategies that the author uses in the treatment of eroticism